2013
DOI: 10.1055/s-0032-1325975
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of a bread bag clip from the duodenum

Abstract: A 73-year-old woman presented with iron deficiency anemia and melena. Biochemical parameters revealed a hemoglobin of 77 g/L and urea 8.5 mmol/L with normal renal indices. She was transfused with 2 units of red blood cells. Gastroscopy revealed a bread clip embedded in D1 (showing the date Friday, 13 April;• " Fig. 1), pinching the distal and proximal duodenal roof fold and dangling like an earring. Attempts to remove the clip by crushing with grasping forceps, cutting with a needle-knife device, and snapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…However, some cases of gastrointestinal tract perforation or bleeding due to the ingestion of bread bag clips have been reported overseas. Between the 1975 and the 2010s, there were 30 cases reported that diagnosed ingestion of bread bag clips in foreign countries [ [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some cases of gastrointestinal tract perforation or bleeding due to the ingestion of bread bag clips have been reported overseas. Between the 1975 and the 2010s, there were 30 cases reported that diagnosed ingestion of bread bag clips in foreign countries [ [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] ].…”
Section: Discussionmentioning
confidence: 99%
“…Sharp pointed objects like toothpicks, stiff wires, food impaction, superabsorbent objects, and objects over 6 cm should be manually removed when they are accidentally ingested [ 4 , 6 ]. The shape of plastic bread bag clips is unique and can result in a trap-like effect, which prevents easy removal once ingested [ 7 ]. There is a report of successful removal of a bread bag clip from the duodenum with biopsy forceps [ 8 ], but in cases where the clips reach the small intestine, retrieval is quite difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Other reported complications include upper gastrointestinal hemorrhage. 5 There are case reports in the literature of endoscopic retrieval of bread bag clips that are embedded in the mucosa of the duodenum. 5,6 A number of endoscopic instruments have been used for this improvised purpose, 5,6 but due to its relative infrequency, the choice of instrument remains up to the individual endoscopist.…”
Section: Discussionmentioning
confidence: 99%
“…5 There are case reports in the literature of endoscopic retrieval of bread bag clips that are embedded in the mucosa of the duodenum. 5,6 A number of endoscopic instruments have been used for this improvised purpose, 5,6 but due to its relative infrequency, the choice of instrument remains up to the individual endoscopist. There have even been reports of fatalities from the complications of bread bag clip ingestion.…”
Section: Discussionmentioning
confidence: 99%